Estimating the portfolio-balance effects of the Bank of Canada's government of Canada Bond Purchase Program - Antonio Díez de los Ríos (Bank of Canada, 2024)
I propose a novel dynamic portfolio-balance model of the yield curve for Government of Canada bonds to evaluate the portfolio-balance effects of the Bank of Canada's Government of Canada Bond Purchase Program. My results suggest that this program, launched on March 27, 2020, in response to the COVID-19 pandemic, lowered the weighted average maturity of the Government of Canada's debt by approximately 1.4 years. This in turn reduced Canadian 10-year and 5-year zero-coupon yields by 84 and 52 basis points, respectively.
Keywords: E43; E52; G12; H63; 330; Asset pricing; Central bank research; Coronavirus disease (COVID-19); Interest rates; Monetary policy